Adjustable Methacrylate Porous Monolith Polymer Layer Open Tubular Silica Capillary Microextraction for the Determination of Polycyclic Aromatic Hydrocarbons. (12th August 2016) - Mugo, Samuel M.; Huybregts, Lauren; Mazurok, James
ABSTRACT: A novel adjustable porous polymer monolith layer open tubular silica capillary microextraction (PLOT-ME) device was fabricated by thermal polymerization of a poly(glycidylmethacrylate- co -ethylene glycol dimethacrylate) (GMA- co -EDMA) polymer film (∼20 µm) within a 250 µm internal diameter silica capillary initiated with 4, 4′-azobis(4-cyanopentanoyl chloride). The polymer film thickness and morphology were controlled by the polymerization time and temperature. The length of the microextraction platform immersed in the sample was adjusted by the sample concentration and sample matrix. Furthermore, since the microextraction platform performance typically degraded with use, the PLOT-ME device affords a new microextraction zone that may be exposed by cleaving off the end. This ability significantly reduces the cost of microextraction for academic and research environments. The performance of the PLOT-ME device was tested for microextraction of polycyclic aromatic hydrocarbons (PAHs): naphthalene, 2, 6-dimethylnaphthalene, anthracene, 9-methylanthracene, and phenanthrene in aqueous media. Linear calibration curves for the PAHs were obtained with correlation coefficients near unity and relative standard deviations from 2 to 20% for PAH standards from 100 to 0.1 µg/L. The limits of detection for the PAHs were between 0.02 and 0.06 µg/L, while the recoveries were from 97 to 104% in lake water. The precision between different PLOT-ME devices was 11%.